Analisis Potensi Bisnis Online Syariah Pada Peningkatan Pendapatan Liebhy Kalamansi Melalui E-Commerce - Kurniawan, Adhadi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This study describes the potential of sharia online business on increasing the income of the company through e-commerce. This research method is a qualitative descriptive approach. Data collection techniques such as observation, documentation and interviews. The results of this study indicate that in online marketing,the business of selling kalamsi liebhy itself goes through the stages.